Nutrient concentrations in tidal creeks as indicators of the water quality role of mangrove wetlands in Southwest Florida. (September 2017) - MacDonnell, Conor P.; Zhang, Li; Griffiths, Lauren; Mitsch, William J.
Graphical abstract: Abstract: Coastal mangroves have the potential to improve the water quality of urban and rural runoff before it is discharged into adjacent coastal bays and oceans; but they also can be impaired by excessive pollutants from upstream. Nutrients (phosphorus and nitrogen), salinity, and other water quality parameters were measured in five mangrove tidal creeks in different hydrogeomorphic and urbanization settings during high and low tides over a calendar year of wet (June and August 2015) and dry (February and April 2016) seasons in the Greater Naples Bay area in Southwest Florida, USA. Nutrient concentrations (ave. ± std error) in the tidal creeks were 0.055 ± 0.008 mg-P/L for total phosphorus (TP) and 0.610 ± 0.020 mg-N/L for total nitrogen (TN), with an average N:P ratio of 11.4:1. Average wet season TP (0.075 ± 0.010 mg-P/L) was significantly higher than the dry season TP (0.033 ± 0.003 mg-P/L; p < 0.01, f = 15.17, f crit = 3.89) and the average wet season TN (0.75 ± 0.03 mg-N/L) was significantly higher than dry season TN (0.52 ± 0.02 mg/L; p < 0.01, f = 64.14, f crit = 3.89), suggesting that urban stormwater runoff is directly or indirectly affecting the nutrient conditions in these mangroves. Significant differences in nutrient concentrations between low tide and high tide were not found for either TP ( p = 0.43, f = .63, f crit = 3.88) or TN ( p = 0.20, f = 1.66, f crit = 3.89). These differences were confirmed by a PCA and cluster analyses, which found differences to be seasonal. We could not conclude from these results whether these five mangrove wetlands were sources nor sinks of nutrients based simply on the measurement of nutrient concentrations. But we illustrated that nutrient concentrations were indicators of the mangroves' hydrogeomorphic settings, their tidal fluxes from Naples Bay, and the Bay's upstream watersheds, and less by direct urban runoff.